Upaya Guru Dalam Meningkatkan Minat Belajar Siswa Kelas XI Pada Mata Pelajaran Fikih Melalui Metode Crossword Puzzle di MA Al-Ahliyah - Nabila Nurazizah; Solihah Bagus; Usep Setiawan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to enhance the learning interest of 11th-grade students at MA Al-Ahliyah Bakan Maja in the Islamic Jurisprudence (Fiqih) subject, specifically on the topic of Jinayat, through the implementation of the crossword puzzle learning method. The research was motivated by the low student interest characterized by minimal participation, low attention levels, and unsatisfactory learning outcomes. Using a qualitative approach in the form of Classroom Action Research with the Kemmis and McTaggart spiral model, the study was conducted over two cycles, each consisting of four meetings. Data were collected through observation, questionnaires, and documentation. Initial observations showed that only 24% of students were actively involved, with an average interest score of 2.1 (low category). After implementing the crossword puzzle in Cycle I, student participation rose to 65%, with an average interest score of 3.2. Improvements in Cycle II, including differentiated puzzle difficulty and a reward system, increased participation to 89% and the average interest score to 4.1. The findings indicate that the crossword puzzle method effectively boosts student interest in Fiqih, creating an active, enjoyable, and collaborative learning environment.